Electronic didactics as a factor in modernization of higher education in pandemic (covid-19) - Ubaydullaeva, Lily (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Global changes in society and education that have recently occurred in pandemic due to intensive use of information and communication technologies suggest a revision of traditional view of didactics. The article considers subject and objectives of e-learning didactics, analyzes terms used in a system of didactic support of e-learning in higher education, and considers promising areas of e-learning anddevelopment of didactic principles